PROJECT-BASED LEARNING FOR DEVELOPING INTEGRATED SKILLS IN A2 LEARNERS - Fakhrullo Madaminov (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Project-based learning (PBL) has been promoted as an instructional approach that fosters meaningful learning, collaboration, and integration of multiple language skills. This paper investigates how PBL can be designed and implemented specifically to develop integrated skills (listening, speaking, reading, writing) in English learners at the CEFR A2 level. Using a systematic review and thematic synthesis of empirical and theoretical literature (2000–2024), the study summarizes PBL principles, examines evidence of effectiveness for language learning, and identifies design features and assessment strategies that optimize learning for A2 pupils. Findings indicate that well-scaffolded PBL units—characterized by clear driving questions, staged scaffolding, multimodal tasks, explicit language focus, and formative assessment—support integrated skill growth and learner motivation. However, the strength of the evidence base for A2-specific outcomes remains emerging and uneven: many studies report positive attitudinal and communicative gains, while robust long-term, CEFR-aligned outcome data are limited. The paper concludes with practical unit designs tailored to A2 classrooms, recommended teacher roles, assessment rubrics, and directions for longitudinal and controlled research.